Liraglutide in the management of type 2 diabetes - Estela Wajcberg; Amatur Amarah (Dove Medical Press, 2010)
Estela Wajcberg, Amatur AmarahPremier Nephrology and Hypertension, Internal Medicine Department, Trinitas Regional Medical Center, Elizabeth, New Jersey, USAAbstract: The pathophysiology of type 2 diabetes has been attributed to the classic triad of decreased insulin secretion, increased insulin resistance, and elevated hepatic glucose production. Research has shown additional mechanisms, including incretin deficiency or resistance in the gastrointestinal tract. Liraglutide is a modified form of human glucagon-like peptide-1. Liraglutide was obtained by substitution of lysine 34 for arginine near the NH2 terminus, and by addition of a C16 fatty acid at the e-amino group of lysine (at position 26) using a γ-glutamic acid spacer. Liraglutide has demonstrated glucose-dependent insulin secretion, improvements in β-cell function, deceleration of gastric emptying, and promotion of early satiety leading to weight loss. Liraglutide has the potential to acquire an important role, not only in the treatment of type 2 diabetes, but also in preservation of β-cell function, weight loss, and prevention of chronic diabetic complications.Keywords: diabetes mellitus, incretin, glucagon-like peptide, insulin resistance